Bemfola® fixed dose pens potentially reduce drug wastage and associated costs of infertility treatment. (2nd October 2018) - Foxon, Graham; Mitchell, Paul; Turner, Nikki; McConnell, Anne; Kendrew, Helen; Jenkins, Julian
Abstract: Bemfola ® is a recombinant follicle-stimulating hormone (FSH) used during infertility treatment. One main differentiator between FSH products is their delivery device; consisting of multi-dose pens (Gonal-f ® ), vials or multi-dose preparations (Menopur ® ), or adjustable daily disposable dose pens (Bemfola ® ). To determine the potential impact of delivery device on drug wastage during infertility treatment this study retrospectively analysed Gonal-f ® and Menopur ® prescription and usage data from five UK clinics. Incurred drug wastage was then compared to potential Bemfola ® drug wastage. Data collected included: (i) number of treatment cycles; (ii) daily FSH dose; (iii) length of treatment; (iv) dose adjustment following ultrasound scan; (v) FSH formulation(s) prescribed and (vi) agonist/antagonist protocol used. Treatment with Gonal-f ® (4078 cycles) and Menopur ® (646 cycles) resulted in an average drug wastage of 160 and 294 IU per treatment cycle. Use of Bemfola ® instead of Gonal-f ® and Menopur ® may reduce the wastage to 104 and 61 IU per cycle, respectively. The use of Bemfola ®, across all 4724 cycles, could result in a drug wastage reduction of up to 376, 800 IUs with an associated cost saving of £100, 011. Bemfola ® is a viable alternative to Gonal-f ® and Menopur ® with its drug delivery system potentially reducing drug wastage and associated costs during infertility treatment.